Use Case Point Activity-Based Costing and Adjusted Function Point for Software Cost Estimation - Ahmad Fauzan Haryono; Andria Farhan; Dewi Khairani; Supardi Razak; Fitri Mintarsih (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Effective software development planning is vital across various industries, and inadequate planning can lead to project failures. A key part of this planning is accurately estimating effort and costs, which is crucial for staying within budget and meeting deadlines. This research compares two methods – Use Case Point Activity Based Costing (with 21 complexity factors) and Adjusted Function Point (with 16 complexity factors) – for estimating costs versus actual values. The analysis reveals that the Use Case Point method had a 23.52% deviation from actual costs, while the Adjusted Function Point method had a 33.35% deviation. These findings provide essential reference points during software project planning, ensuring estimates closely align with actual values based on project-specific attributes. This deviation underscores the importance of precision and selecting appropriate methodologies tailored to each project’s unique characteristics. Ultimately, this research equips businesses and project managers with a robust financial prudence framework and enhances the likelihood of project success.